(untitled) (KMC Journal, 2025)
This study examines Nepal’s Balance of Payments (BOP) from 1998/99 to 2022/23 under its fixed exchange rate regime with the Indian Rupee (INR). Using the ARDL model, well suited for small samples and mixed-integration data along with an ECM, this study investigates the casual impact of the INR/USD exchange rate, remittance inflows, and import levels on Nepal’s BOP. The results reveal a significant long-run cointegration among variables. Findings show long-run cointegration: a 1% INR depreciation versus the USD boosts BOP by NPR 6.32 billion, enhancing export competitiveness. A 1% rise in imports cuts BOP by NPR 27.47 billion, reflecting trade deficits and remittances increase BOP by NPR 15.22 billion, stabilizing it. The study highlights Nepal’s vulnerability to INR fluctuations and import dependency, advocating for export diversification, remittance-driven investments, and strategic import controls. Policy recommendations emphasize enhancing forex reserves, diversifying trade partners, and strengthening monetary coordination with India to mitigate external vulnerabilities. These insights offer practical guidance for sustaining BOP stability in economies with pegged exchange rate regimes.